MAJALAH AL-ISLAH DAN MASYARAKAT MELAYU TAHUN 70-AN (Al-Islah Magazine and Malay Community in 70s) - Abdul Hamid, Faisal@Ahmad Faisal; Jalani, Hamidah (Journal of Al-Tamaddun, 2011)
Backwardness of the Malay community is the core issue since the West colonial left Malaysia and still being discussed to this day. Statements such as "Malays Backward" and "Malays Poverty" are often expressed in Malay magazines and political stage. Efforts and plans have been and are still being implemented to remove the Malays from poverty. Continued efforts should not be seen from the contributions of a particular party simply by denying some of the other efforts that have contributed towards the development. Therefore, this paper will discuss the ideas and comments from the al-Islah magazine to raise community awareness towards progress and development of the nation. Al-Islah Magazine (Feb 1970 - August 1974) is the subject of discussion in this paper could be regarded as a platform to invite Muslim scholars to rise against the backwardness of the Malay community. There are three issues addressed in this paper that include the issue of education, economic and social, which are among the core issue in the Malay community.